1935 S.D. Sess. Laws 355, ch. 208, &sect - (:unkn) unknown (My University, 1935)
No person shall deliver a pistol to any person under the age of eighteen or to one who he has reasonable cause to believe has been convicted of a crime of violence, or is a drug addict, an habitual drunkard, or of unsound mind."
8
Keywords: TRANSFER - MINORS